Termografia infravermelho na estimativa de conforto térmico de frangos de corte - do Nascimento, Guilherme R.; Nääs, Irenilza A.; Baracho, Marta S.; Pereira, Danilo F. [UNESP]; Neves, Diego P. (My University, 2014)
Poultry facilities must provide an environment that ensures thermal comfort allowing the animal to express its genetic potential for production; and new tools are being applied to measure the thermal comfort, especially thermal cameras. The objective of this study was to evaluate the association of the surface temperature of the birds with those from the facilities, and estimate the sensible heat transfer. For this, the thermal conditions of rearing in two aviaries with different ventilation systems, during the period of March to April 2011 were recorded. The aviaries were divided into six quadrants for the registration of surface temperatures obtained using an infrared thermal camera. In each quadrant the ambient temperature, relative humidity and wind velocity during the obtention of images were also recorded. It was observed that the surface temperatures of birds are associated with the surface temperature of the rearing facilities (side curtains, roof and litter). In aviary with negative pressure higher wind speeds compared to the conventional one were recorded and; therefore, allowed a higher sensible heat transfer by birds, suggesting that this provided better conditions for thermal comfort.
Infrared thermography in the estimation of thermal comfort of broilers
Keywords: Surface temperature; Thermoregulation; Welfare